Tension pneumoperitoneum and generalized subcutaneous emphysema due to subhepatic suction drainage functioning as an air injector - Marella, Muzio; Tomalino, Dante; Cardoso Lareo, Federico; Quiroz (h), Juan Darío (Cirugía del Uruguay, 1975)
A case is presented of hypertensive pneumoperitoneum with subcutaneous emphysema and serious general condition, produced by an aspirator connected to a peritoneal d